Mythological creatures : a classical bestiary : tales of strange beings, fabulous creatures, fearsome beasts, & hideous monsters from Ancient Greek mythology - Curlee, Lynn. (New York : Atheneum Books for Young Readers, 2008)
An illustrated guide to the beasts often found in ancient myths that describes each creature's origins and what role it has played in world mythology.
Kirkus Review
6.8
3-6.
3-6
Keywords: Animals, Mythical -- Juvenile literature; Animals -- Folklore -- Juvenile literature; Bestiaries -- Juvenile literature; Mythology, Classical -- Juvenile literature; Animals, Mythical; Animals -- Folklore; Bestiaries; Mythology, Classical; Animals -- Folklore; Bestiaries; Classical mythology; Mythical animals